Reward System as a Strategy to Enhance Employees Performance in an Organization - Francis, Felix; Zirra, Clifford Tizhe Oaya; Charles J. , Mambula I (Archives of Business Research, 2020)
This research paper is about reward system as a strategy to enhance employee’s performance in an organization. The research means this needs of an organization and its employee, their low productivity behavior and therefore the way this behavior are often change through reward to enable their performance boost the organization needs. The research was administered through constructive analysis from different articles that base on reward system. Descriptive and exploratory research designs were used for the purpose of this research work. The study observed that there is positive relationship between rewards and employees performance, productivity and retention in an organization. However, rewards system, in an organization should be designed with a constructed strategies that need to be a neighborhood of organization‘s culture.